Perbedaan Kondisi Fisik Pemain Sepak Bola Berdasarkan Lingkungan Pembinaan - Irawan, Safri; Haryani, Meri; Prasetyo, Agung; Haryanto, Arief Ibnu; Refiater, Ucok Hasian; Kadir, Suprianto (Universitas Negeri Gorontalo, 2025)
Physical condition is an essential component in achieving optimal performance in football. This study aims to systematically review various research discussing the physical condition aspects of football players at different age levels and competition levels. The research method uses a literature review approach on 10 national scientific articles published within the last five years. The analysis focuses on dominant physical condition components in football, such as muscle strength, endurance, speed, agility, flexibility, and leg power. The review results indicate that most football players at school, club, and academy levels have physical conditions categorized as moderate to good, although specific aspects still need improvement depending on playing position and training level. This study concludes that improving physical condition should be specific, measurable, and sustainable according to the characteristics of the football game.